Long Non-coding RNA ASNR Targeting miR-519e-5p Promotes Gastric Cancer Development by Regulating FGFR2 - Chen, Zihao; Li, Yong; Tan, Bibo; Li, Fang; Zhao, Qun; Fan, Liqiao; Zhang, Zhidong; Zhao, Xuefeng; Liu, Yu; Wang, Dong (Frontiers in Cell and Developmental Biology, 2021)
Gastric cancer (GC), as a common gastrointestinal tumor, is an important cause of death from cancer all around the world. Long non-coding RNAs (lncRNAs), a novel class of transcripts, have attracted great attention of researchers. However, the mechanisms of the clinical significance of most lncRNAs in human cancer are mainly undocumented. This research desires to explore the clinical significance, biological function, and mechanism of Lnc_ASNR (apoptosis suppressing-non-coding RNA) in GC. Cell proliferation, cell cycle, cell migration, and invasion abilities were respectively determined by 3-(4,5)-dimethylthiahiazo (-z-y1)-3,5-di-phenytetrazoliumromide (MTT), flow cytometry, wound healing, and Transwell assay (Sigma-Aldrich, St. Louis, MO, United States). The association of Lnc_ASNR, miR-519e-5p, and fibroblast growth factor receptor 2 (FGFR2) was evaluated via luciferase reporter experiments. The tumor xenograft assay was conducted to confirm the results of cell experiments. High expressed Lnc_ASNR was detected in both GC cells and tissues using qRT-PCR. Downregulated Lnc_ASNR could reduce proliferation, migration, and invasion in GC cells, while upregulated Lnc_ASNR could promote the cell proliferation, migration, and invasion. Moreover, the effect of Lnc_ASNR on migration and invasion ability is closely related to epithelial-mesenchymal transition (EMT). The bioinformatics analysis, luciferase assay, and Western blot demonstrated that Lnc_ASNR inhibited miR-519e-5p expression but increased FGFR2 expression. Lnc_ASNR and FGFR2 were both targeted to miR-519e-5p, and they were negatively correlated with the expression of miR-519e-5p. All investigations indicated that Lnc_ASNR functioned as a ceRNA targeting miR-519e-5p and facilitated GC development by regulating the pathway of miR-519e-5p/FGFR2.